A new compression system for treatment of venous leg ulcers: a prospective, single-arm, clinical trial (FREEDOM). (2nd September 2022) - Senet, Patricia; Addala, Azeddine; Léger, Philippe; Chahim, Maxime; Malloizel, Julie; Blaise, Sophie; Sauvadet, Anne; Tacca, Olivier; Stücker, Markus; Dissemond, Joachim
Abstract : Objective: To evaluate the efficacy, tolerability and acceptability of a new multicomponent compression system in one bandage for the local treatment of patients with venous leg ulcers (VLUs). Method: This was an international, prospective, non-comparative, clinical trial, conducted in France and Germany. Eligible participants had a VLU with a wound area of 2–20cm 2, lasting for a maximum of 24 months. For a period of 6 weeks, patients were treated with a new multicomponent compression system in one bandage which was worn day and night, providing high working pressure and moderate resting pressure (UrgoK1). Clinical assessments, wound measurement and photographs were planned at weeks 1, 2, 4 and 6. The primary endpoint was the relative wound area reduction (RWAR) after 6 weeks of treatment. Secondary endpoints included wound closure rate, oedema resolution, change in patient's health-related quality of life (HRQoL), acceptability, adherence to the compression therapy, local tolerance, and physician's overall satisfaction with the evaluated compression system. Results: A cohort of 52 patients (52% female, mean age 75.4±13.0 years) with VLUs, including oedema in 58% of cases, were recruited from 22 centres. At baseline, 42 patients had already been treated with a different compression system. VLUs had been present for 5.6±4.9 months and had a mean area of 5.7±4.3cm 2 . After 6 weeks of treatment, a median RWAR of 91% (interquartile range: 39.4; 100.0) was achieved. Wound closure was reported in 35% of patients. A RWAR ≥40% at week 4, predictive of wound healing at 12 weeks, was achieved in 62% of patients. At the final visit, oedema present at baseline was resolved in 57% of patients. Substantial improvements in the HRQoL of the patients were reported with a decrease of the pain/discomfort and anxiety/depression dimensions. Comfort in wearing the evaluated system was reported as 'very good' or 'good' by 79% of patients, resulting in a high patient adherence to compression therapy. Compared to previous compression systems, half of the patients reported more ease in wearing shoes, and greater satisfaction and comfort with this new system. Nine non-serious adverse events related to the device or its procedure occurred in seven patients. At the final visit, the majority of the physicians were 'very satisfied' or 'satisfied' with the new compression system overall. Conclusion: The new multicomponent compression system in one bandage has been shown to promote rapid healing of VLUs, reduce oedema, improve HRQoL and to be well tolerated and accepted. It appears to be a viable alternative to existing compression systems.